Kualitas Fisik Biskuit Ransum Pakan Ternak Kambing Berbahan Perekat Sari Serat Buah Koli (Borassus flabellifer) - Jannah, Fatahul; Joris, Lily; Fredriksz, Shirley (Universitas Pattimura, 2024)
This study aims to obtain a ration feed biscuit product to meet the nutritional needs of goats and to obtain a formula and ration feed biscuit product made from koli fiber juice adhesive with different percentages. This research was conducted at the Feed Technology and Engineering Laboratory, Department of Animal Husbandry, Faculty of Agriculture, Pattimura University, Ambon. Data analysis used Completely Randomized Design (CRD) with 4 treatments and 4 replicates, The treatments in this study were as follows; P0 = no added chole fiber juice adhesive material, P1 = addition of 2.5% chole fiber juice adhesive material, P2 = addition of 5% chole fiber juice adhesive material, P3 = addition of 7.5% chole fiber juice adhesive material. The changes observed were specific gravity, color, density, thickness and water absorption. The results showed that the treatment had a significant effect (P<0.05) on density but no significant effect (P>0.05) on specific gravity, color, thickness and water absorption. The conclusion of this study is that feed biscuits with the use of 5% koli fiber juice adhesive material show the best results with average values where the results are brown color, specific gravity 0.18, density 0.00019, thickness 30.36 and water absorption 3.48.